Mapping Chemistry Learning Barriers in the Context of Islamic Higher Education: Insights from Pre-Service Chemistry Teachers - Fibonacci, Anita; Kadarohman , Asep; Hernani , Hernani; Roslan , Roslinawati; Drastisianti , Apriliana (Journal of Learning Improvement and Lesson Study, 2025)
is known about how these barriers are experienced within Islamic university contexts. This study investigates such barriers among pre-service chemistry teachers in an Islamic university background. Employing a qualitative case study design, 53 participants were purposively selected and provided data through open-ended questionnaires and in-depth interviews. Data were analyzed using Braun and Clarke’s thematic analysis with NVivo 12 support. The results indicated that organic chemistry was the course most frequently perceived as difficult according to Pre-Service Chemistry teachers (PCTs) in an Islamic University. Building on this finding, thematic analysis identified four main themes as underlying barriers to learning organic chemistry: (a) intrinsic content challenges, (b) high cognitive demands, (c) motivational barriers, and (d) lack of supportive learning tools and approaches. These results indicate that pre-service chemistry teachers’ barriers in learning chemistry are multifaceted, extending beyond content knowledge to include cognitive and affective dimensions as well as contextual limitations in Islamic higher education. The results provide insights for designing pedagogical strategies that infusing Islamic values in science leaning to lead inner motivation, and offer accessible learning tools such as tangible 3D molecular models and digital simulations to support deeper engagement for complex concepts like organic chemistry courses.